Population structure and growth of the beaked clam Eumarcia paupercula (Bivalvia, Veneridae) in Maputo Bay, Mozambique. Issue 4 (17th December 2019) - Mugabe, ED; Amoda, CA; Griffiths, CL
Abstract : The edible beaked clam Eumarcia paupercula (Holten, 1802) is an abundant component of the intertidal infauna in Maputo Bay, Mozambique, and is an important source of food and income for local communities. This study investigates the population structure and estimates the growth rate of E. paupercula on a highly exploited tidal flat. Between November 2012 and April 2014, population structure was tracked by monitoring monthly length and density distributions, and growth rate was estimated using both mark-recapture experiments and length-frequency analysis (LFA). The population structure can be polymodal, bimodal or unimodal, as new cohorts of clams recruit to the population and older ones are fished or die out. The von Bertalanffy growth function Lt = 40.5 [1 – e –1.65(t – 0.03) ] revealed that E. paupercula has a fast growth rate, equivalent to a phi-prime index (ϕ′) of 3.43, and a short lifespan of 1.97 years, similar to those of most other tropical venerid species. This article highlights that temporal population dynamics are strongly influenced by collection and reproductive patterns, and that single environmental parameters do not explain the patterns of growth. Understanding these factors will greatly facilitate development of management measures aimed at ensuring future sustainable exploitation of this species.